Legal Considerations of the Notary Supervisory Board Regarding the Concept of Carefulness and Legal Consequences For Deeds Made Based on False Information - Ahmad Wildani Taufiqi; Rachmi Sulistyarini; Fathul Laila (State Islamic University of North Sumatra Indonesia, 2025)
This research examines the legal responsibility of notaries for authentic deeds made based on false statements from the perspective of the Regional Supervisory Council of Southeast Sulawesi. The main issues explored are how the MPW interprets the phrase